Types of Code-switching in Nofitah Official's Instagram Caption - Lestari, Nidia Ayu; Ni Made, Verayanti Utami; Putu, Devi Maharani (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
This research is aimed to solve the research problems. The first problem is aimed to classify the sorts of code-switching observed in Nofitah official's Instagram, and the second is aimed to analyze the reason why the speaker code-switch her utterances. The research used a descriptive qualitative method. In order to identify the code-switching, this research utilized theories proposed by Appel and Muysken (1987) to classify the types of code-switching and also the theory proposed by Hoffman (1991) to describe the reasons for code-switching The end result of this research indicates that all types of code-switching and five reasons for code-switching were found. The dominant type that occurred in this research is inter-sentential switching. It happens due to the fact that Nofitah looks extra blissful when using words, clauses, and phrases in a sentence to convey a motivational message. Five reasons for code-switching were found. The most dominant cause is the intention of clarifying the speech content for the interlocutor. This happened because Nofitah felt free and was freer to disclose what she felt in a language that was not her daily language.